2008
DOI: 10.1016/j.bbamcr.2008.05.015
|View full text |Cite
|
Sign up to set email alerts
|

YY1 restrained cell senescence through repressing the transcription of p16

Abstract: The transcription factor YY1 has been implicated to play a role in cell growth control. In this report, we demonstrate that YY1 was able to suppress NCI-H460 cell senescence through regulating the expression of p16(INK4a), a cyclin-dependent kinase inhibitor. We also show that YY1 participated in the repression of p16(INK4a) expression in 293T cells through an epigenetic mechanism involving histone acetylation modification. Specifically, HDAC3 and HDAC4 inhibited the p16(INK4a) promoter activity. The chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…However, YY1 expression can similarly regulate cell growth by interaction with Rb [8], [12], [44]. YY1 can also impact senescence by regulating p16 INK4a [45], and can increase HoxB7 expression directly involved in tumor progression [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, YY1 expression can similarly regulate cell growth by interaction with Rb [8], [12], [44]. YY1 can also impact senescence by regulating p16 INK4a [45], and can increase HoxB7 expression directly involved in tumor progression [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that various transcription factors, such as Ets and Bmi1, play critical roles in the transcriptional regulation p16 gene5. Our earlier studies showed that the histone acetyltransferase p300 recruited by Sp1 stimulated p16 transcription through inducing the H4 hyperacetylation on p16 gene, whereas HDAC3/4 inhibited the p16 promoter activity via the transcription factors YY1 and ZBP-89678.…”
mentioning
confidence: 96%
“…YY1 exerts its effects on genes involved in these processes via its ability to initiate, activate, or repress transcription depending upon the context or recruited cofactors in which it binds [15,16]. One such family of cofactors are the histone deacetylases which have been shown to bind YY1 and repress transcription when targeted to promoters [17]. YY1 has been shown to interact with p300, PCAF and CBP, all which posses the histone acetyltransferase (HAT) activity [17].…”
Section: Introductionmentioning
confidence: 99%
“…One such family of cofactors are the histone deacetylases which have been shown to bind YY1 and repress transcription when targeted to promoters [17]. YY1 has been shown to interact with p300, PCAF and CBP, all which posses the histone acetyltransferase (HAT) activity [17]. YY1 may thus activate transcription by its recruitment of HAT proteins and repress transcription by recruiting HDACs.…”
Section: Introductionmentioning
confidence: 99%